2012
DOI: 10.1126/scitranslmed.3004062
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Induction of Rac1b, a Key Effector of Lung Cancer Progression

Abstract: Lung cancer is more deadly than colon, breast, and prostate cancers combined, and treatment improvements have failed to improve prognosis significantly. Here, we identify a critical mediator of lung cancer progression, Rac1b, a tumor-associated protein with cell-transforming properties that are linked to the matrix metalloproteinase (MMP)–induced epithelial-mesenchymal transition (EMT) in lung epithelial cells. We show that expression of mouse Rac1b in lung epithelial cells of transgenic mice stimulated EMT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 66 publications
6
94
0
Order By: Relevance
“…RAC1b, a splice variant of RAC1 that predominantly exists in the GTP-bound active form, has been previously shown to be highly expressed in breast and colon cancers (Jordan et al 1999;Schnelzer et al 2000). More recently, two papers reported that RAC1b promotes K-rasinduced lung tumorigenesis, and that RAC1b stimulates epithelial-mesenchymal transition and spontaneous tumor formation (Stallings-Mann et al 2012;Zhou et al 2012). We observed near twofold up-regulation of total RAC1 expression levels in all three lung tumors.…”
Section: Differential Isoform Usage Revealed By Rna-seqsupporting
confidence: 61%
“…RAC1b, a splice variant of RAC1 that predominantly exists in the GTP-bound active form, has been previously shown to be highly expressed in breast and colon cancers (Jordan et al 1999;Schnelzer et al 2000). More recently, two papers reported that RAC1b promotes K-rasinduced lung tumorigenesis, and that RAC1b stimulates epithelial-mesenchymal transition and spontaneous tumor formation (Stallings-Mann et al 2012;Zhou et al 2012). We observed near twofold up-regulation of total RAC1 expression levels in all three lung tumors.…”
Section: Differential Isoform Usage Revealed By Rna-seqsupporting
confidence: 61%
“…One particular example is the tumor-related splicing variant Rac1b, an isoform of the signaling GTPase Rac1 (Matos et al 2003), in which a usually skipped exon 3b is retained. The resulting protein isoform Rac1b is overexpressed in a specific subtype of colorectal tumors and required to sustain tumor cell survival (Jordan et al 1999;) but was also reported in breast, lung, and thyroid tumors (Schnelzer et al 2000;Radisky et al 2005;Liu et al 2012;Stallings-Mann et al 2012;Silva et al 2013;Zhou et al 2013). Interestingly, Rac1b was found to be predominantly in the signaling-competent GTP-bound conformation (Schnelzer et al 2000;Matos et al 2003;Fiegen et al 2004;Radisky et al 2005), so that small changes in its expression level yield significant cellular responses.…”
Section: Introductionmentioning
confidence: 98%
“…5). Moreover, RAC1b overexpression has been implicated in the induction of EMT (40,41). EMT is a form of epithelial plasticity that has been associated with tumor metastasis and, accordingly, RAC1b was reported to have a key role in the malignant progression of breast and lung tumors (28,36,41).…”
Section: Discussionmentioning
confidence: 99%